Homozygous deletion of CDKN2A in malignant mesothelioma: Diagnostic utility, patient characteristics and survival in a UK mesothelioma centre. (December 2020) - Marshall, Kelly; Jackson, Susan; Jones, Jennifer; Holme, Jayne; Lyons, Judith; Barrett, Emma; Taylor, Paul; Bishop, Paul; Hodgson, Clare; Green, Michael; Telford, Nicholas; Evison, Matthew
Highlights: This is the largest study of p16 FISH testing in real-world practice (n = 216). 60 % of mesotheliomas harboured a homozygous deletion of CDKN2A. There were no false positive results using a cut-off of >20 % cells displaying CDKN2A deletion. The highest proportion of cells with CDKN2A deletion in benign pleuritis was 13 %. P16 FISH expands the diagnostic reach in cases of suspected but not definitive mesothelioma. Abstract: Background: Detection of homozygous deletion of the p16 gene (CDKN2A) by fluorescence in situ hybridization (FISH) has been investigated as an ancillary technique in the diagnosis of malignant mesothelioma. Method: This retrospective study reviewed the results of all p16 FISH tests performed at a regional mesothelioma centre from February 2012 to November 2019 in cases of possible mesothelioma to examine the diagnostic utility of this test as well as patients characteristics and survival in p16 FISH positive mesothelioma versus p16 FISH negative mesothelioma. Results: P16 FISH testing was requested in 216 pathological samples in the study period. The test failure rate was 4% (10/216). Median time from request to result was 10 days (IQR 7–13, range 1–30). The sensitivity, specificity, NPV and PPV were 60 %, 100 %, 39 % and 100 % respectively. There were no false positive results and this genetic aberration was only detected in cases of mesothelioma. The prevalence of p16 FISH positive mesothelioma was higher in cytological specimens compared to histological specimens (75 % vs 58 %, p = 0.03) and lower in women compared to men (33 % vs 66 %, p = 0.003). P16 FISH positive mesothelioma was associated with significantly worse survival (median overall survival 285 vs 339 days, p = 0.0018). This remained significant after adjusting for confounding variables (OR 4.4, 95 %CI 1.84–11.14, p = 0.001). Conclusions: In this study, 60 % of mesotheliomas harbour a homozygous deletion of CDKN2A and can be accurately, reliably and efficiently identified by p16 FISH testing. This test can be embedded within routine practice in mesothelioma pathways to enhance diagnostic accuracy.